Two-step sequence of acetalization and hydrogenation for synthesis of diesel fuel additives from furfural and diols. - Patil, Anil; Shinde, Suhas; Kamble, Sanjay; Rode, Chandrashekhar, V (Energy & Fuels, 2019)
Acetalization of diols with furfural and subsequent hydrogenation of acetal products provided potential fuel additives that could be blended into commercial diesel. Glycerol could be an interesting polyol for acetalization with furfural due to its low cost, and it is produced as a byproduct in very large amount in the process of biodiesel production. In this work, glycerol acetalization with furfural has been selected as a model reaction. Acetalization reaction was performed under neat conditions (solventless) with 1:1 molar ratio of furfural and glycerol at room temperature over various acid catalysts, including homogeneous and heterogeneous acids. Among several catalysts, Zr-Mont, a heterogeneous solid acid having controlled acidity, gave as high as 78% isolated yield of acetal products. Interestingly, acetal products can be isolated in pure form by performing extraction using cyclohexane that enables selective extraction of product, and unreacted glycerol and furfural were left in aqueous phase, which can be recycled. Further, to make fuel components from isolated acetal product of glycerol and furfural, hydrogenation was performed over a series of supported noble-metal catalysts under low H-2 pressure at room temperature. Among them, 5% Pd/C showed very high activity for ring hydrogenation that resulted in high yield of hydrogenation products. However, hydrogenated product contains free hydroxyl group that needs to be subsequently etherified or acetylated. Interestingly, etherified derivative was obtained in high yield compared to acetylated derivative. In addition, several other diols were treated with furfural and their products were subsequently hydrogenated over 5% Pd/C under very low H-2 pressure. The properties of resulting compounds were investigated so as to find most suitable candidates as additives to commercial diesel.